(untitled) (Cardiovascular Journal, 2022)
Background: Serum troponin is an exquisitely sensitive marker of myocardial injury and is necessary for establishing the diagnosis of Myocardial Infarction particularly non-ST elevation myocardial infarction (NSTEMI). However, the relation of troponin-I level with left ventricular systolic dysfunction following first episode of NSTEMI are still not examined in our population. Therefore, to determine the relationship of serum troponin I with left ventricular ejection fraction after first episode of NSTEMI was set as an objective of the study. Methods: This cross sectional analytical study was conducted on 160 patients. They were divided into the two groups (80 patients in each group): Group-A (Troponin I level e” 0.4 ng/ml) high risk group and Group-B (Troponin I level < 0.4 ng/ml) low risk group. Left ventricular systolic dysfunction was defined as ejection fraction (EF%) < 50% calculated by modified Simpson’s method on transthoracic echocardiography. Association of troponin-I level with left ventricular systolic function was determined. Results: Among a total 160 patients, no significant variation across the group A and B in terms of age, gender and occupation (p>0.05 in all cases). Median serum troponin I of group A was 7.24 (range: 0.41- 58.25) and group B was 0.21(range: 0.12-0.39). Left ventricular EF was significantly lower in higher troponin I group (Group A-45.95±10.28 vs. Group B-56.30±7.78; p<0.05) and it was associated with higher proportion of left ventricular dysfunction (p<0.05). Conclusion: Serum troponin-I can be considered as a predictor of the left ventricular systolic dysfunction in first episode of Non-ST elevation myocardial infarction patients. Cardiovasc j 2022; 15(1): 42-48